2012
DOI: 10.1155/2012/352059
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase 3B Gene Promoter and Interleukin-1 Receptor Antagonist Polymorphisms in Childhood Immune Thrombocytopenia

Abstract: Primary immune thrombocytopenia (ITP) is one of the most common blood diseases as well as the commonest acquired bleeding disorder in childhood. Although the etiology of ITP is unclear, in the pathogenesis of the disease, both environmental and genetic factors including polymorphisms of TNF-a, IL-10, and IL-4 genes have been suggested to be involved. In this study, we investigated the rs2424913 single-nucleotide polymorphism (SNP) (C46359T) in DNA methyltransferase 3B (DNMT3B) gene promoter and the VNTR polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(48 reference statements)
3
16
0
Order By: Relevance
“…However, the authors did not find any significant difference between ITP and healthy control groups in terms of IL-10 (-1082,-819,-592) and IL-6 (-174) polymorphisms. Similar results regarding IL-1 Ra polymorphism were found in a study conducted by Pesmatzoglou et al [5] who investigated VNTR polymorphism of IL-1 receptor antagonist (IL-1 Ra) intron-2 in 32 children with the diagnosis of ITP and 64 healthy individuals in Greece. They reported that children with ITP had a significantly higher frequency of genotype A1A2 compared to control group and that the presence of allele A2 seems to increase 2.12 times the risk for development of ITP, thus assuming that IL-1 Ra polymorphism may be involved in the pathogenesis of ITP.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, the authors did not find any significant difference between ITP and healthy control groups in terms of IL-10 (-1082,-819,-592) and IL-6 (-174) polymorphisms. Similar results regarding IL-1 Ra polymorphism were found in a study conducted by Pesmatzoglou et al [5] who investigated VNTR polymorphism of IL-1 receptor antagonist (IL-1 Ra) intron-2 in 32 children with the diagnosis of ITP and 64 healthy individuals in Greece. They reported that children with ITP had a significantly higher frequency of genotype A1A2 compared to control group and that the presence of allele A2 seems to increase 2.12 times the risk for development of ITP, thus assuming that IL-1 Ra polymorphism may be involved in the pathogenesis of ITP.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have investigated so far the association between cytokine gene polymorphisms and different immune-inflammatory diseases such as psoriasis, SLE, and rheumatoid arthritis [5,15,[41][42][43]. Furthermore, IL-17F gene is an excellent candidate for chronic inflammatory disease including ulcerative colitis, Behcet's disease, asthma, and inflammatory bowel disease [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially functional polymorphisms were identified to meet the following criteria: 1) minor allele frequency (MAF) ≥0.05 in Han Chinese Beijing; 2) located in 5′-untranslated regions (UTR), 5′ near gene, exon, and 3′-UTR. The rs2424913 SNP with an MAF 1.2% is located -149 bp from the DNMT3B gene promoter transcription start site, and is associated with childhood immune thrombocytopenia (ITP) [15]. Another rs13428812 is an intronic SNP associated with CD [12].…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…The rs2424913 of the DNMT3B gene ��� ��g��fi����l� ���������d w��� � ��g���v� ���k �� ��l������l cancer development in the African population (37). Although the genotype distribution of DNMT3B rs2424913 demonstrated �� ��g��fi���� d���������� b��w��� ��� ���ld��� w��� ������ thrombocytopenia (ITP) and the healthy individuals, the ���q������� �� ��� T �ll�l� w��� ��g��fi����l� ��������d �� children with ITP (38). Conversely, Piotrowski et al (39) identified that the rs1550117 of DNMT3A �x��b���d � ��g��fi���� ����������� w��� SLE �� � P�l��� ����l����� w��� compared with healthy individuals, which indicated that this SNP may protect against SLE development.…”
Section: Discussionmentioning
confidence: 99%